Seroprevalence and associated risk factors Mycobacterium avium subsp. paratuberculosis in cattle from Villavicencio - Guzman-Barragan, Blanca (2023)
The study aimed to estimate the seroprevalence and risk factors for Mycobacterium avium subsp. paratuberculosis in Villavicencio, Colombia. Blood samples were taken from 1000 dual-purpose cattle in 24 farms. The diagnosis was done by indirect ELISA for the detection of antibodies. Risk factors were determined using univariate and multivariate tests. The overall seroprevalence of Mycobacterium avium subsp. paratuberculosis was 52.4% and that of the herd was 100%. Female sex, animals older than 4 years, and sale of animals were identified as risk factors. The zebu breed was considered as a protection factor.